Verbal Memory and Visual Perception in early Alzheimer’s disease: Contribution of new diagnostic tools for new classification criteria - Oliveira, Raquel Maria Baptista Lemos Guerra de (2016)
Tese de doutoramento em Psicologia, na especialidade de Neuropsicologia, apresentada à Faculdade de Psicologia e de Ciências da Educação da Universidade de Coimbra